From Asceticism to a Gospel of Prosperity: The Case of Full Gospel Mission Cameroon - Mbe, Akoko R. (Journal for the Study of Religion, 2004)
Within the last decade, the Pentecostal terrain in Cameroon has witnessed a rise in new groups coming in, with the prosperity doctrine as their economic message. Within this period Full Gospel Mission, one of the older generations of Pentecostal groups in the country, which adopted complete asceticism as an economic message from the on set, has embraced accumulation. This change has enabled the church and its members to engage in business ventures and it has also brought members closer to non-members in material display. This paper examines the external and internal factors, which have pushed the Mission to embrace accumulation and concludes that the smooth transition has been enhanced by the economic crisis affecting Cameroon.
free